Early pregnancy thyroid hormone reference ranges in Chilean women: the influence of body mass index. (29th June 2016) - Mosso, Lorena; Martínez, Alejandra; Rojas, María Paulina; Latorre, Gonzalo; Margozzini, Paula; Lyng, Trinidad; Carvajal, Jorge; Campusano, Claudia; Arteaga, Eugenio; Boucai, Laura
Summary: Objective: Thyroid dysfunction and obesity during pregnancy have been associated with negative neonatal and obstetric outcomes. Thyroid hormone reference ranges have not been established for the pregnant Hispanic population. This study defines thyroid hormone reference ranges during early pregnancy in Chilean women and evaluates associations of body mass index (BMI) with thyroid function. Design, patients, measurements: This is a prospective observational study of 720 healthy Chilean women attending their first prenatal consultation at an outpatient clinic. Thyroid function [TSH, Free T4, Total T4 and antithyroid peroxidase antibodies (TPOAb)] and BMI were assessed at 8·8 ± 2·4 weeks of gestational age. Results: Median, 2·5th percentile (p2·5), and 97·5th percentile (p97·5) TSH values were higher, while median, p2·5, and p97·5 free T4 values were lower in obese patients compared with normal weight patients. Obesity was associated with a median TSH 16% higher ( P = 0·035) and a median free T4 6·5% lower ( P < 0·01) than values from patients with normal weight. BMI had a small, but statistically significant effect on TSH ( P = 0·04) and free T4 ( P < 0·01) when adjusted by maternal age, TPO antibodies, parity, sex of the newborn, gestational age and smoking. In all TPOAb (‐) patients, median (p2·5‐p.97·5) TSH was 1·96 mIU/l (0·11–5·96 mIU/l) and median (p2·5‐p.97·5) free T4 was 14·54 pmol/l (11·1 – 19·02 pmol/l). Applying these reference limits, we found a prevalence of overt and subclinical hypothyroidism of 0·9% and 3·05% respectively. Conclusions: TSH distributes at higher values and free T4 at lower values in obese pregnant women compared to normal weight pregnant women. Thyroid hormone reference ranges derived from Chilean patients with negative TPOAb are different from the fixed internationally proposed reference ranges and may be used in the Hispanic population.